A compilation and development of spatial and temporal profiles of high-resolution emissions inventory over Thailand - Chatchawan Vongmahadlek (2018)
Thailand, located in Southeast Asia, has both anthropogenic and natural emission sources. It is important to develop an emission information system to provide fundamental data to support emission control strategies and air quality studies. In this research, emissions were compiled for the year 2005. Emission sources cover key anthropogenic and natural emission sources. The methodology to calculate emissions is based on the bottom-up approach using local specific data. For gaseous species, annual emission estimation is found as follows: 9465.9 Gg of carbon monoxide, 2583.1 Gg of nonmethane volatile organic compounds, 886.0 Gg of sulfur dioxide, 790.3 Gg of oxides of nitrogen, and 439.2 Gg of ammonia. For aerosol species, annual emission estimations are 1277.4 Gg of particulate matter smaller than or equal to 10 μm in aerodynamic diameter, 325.5 Gg of organic carbon, and 136.4 Gg of black carbon. The intercomparison with literature shows an acceptable agreement of annual estimation. Emissions are projected until the year 2027 based on a Business-as-Usual scenario from governmental trends. Spatial allocations with 1- by 1-km resolution and temporal (i.e., monthly, weekly, and diurnal) allocation profiles are also developed to investigate the variation of emissions. Copyright 2009 Air & Waste Management Association.